2021
DOI: 10.1039/d1nr00957e
|View full text |Cite|
|
Sign up to set email alerts
|

A mesoporous polydopamine nanoparticle enables highly efficient manganese encapsulation for enhanced MRI-guided photothermal therapy

Abstract: Theranostic agents based on magnetic resonance imaging (MRI) and photothermal therapy (PTT) play an important role in tumor therapy. However, available theranostic agents are confronting great challenges in the issues...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…To overcome this limitation, manganese is a good substitute because of its inherent advantages, such as low intrinsic toxicity and effective positive contrast enhancement effect [ 117 , 118 ]. Wu et al [ 119 ] synthesized MPDA NPs (called MPDAPs) using the soft template method and then complexed Mn 2+ to obtain MPDAPs/Mn. In vitro infrared imaging analysis revealed that the photothermal conversion efficiency of MPDAPs/Mn was as high as 45.2%.…”
Section: Cancer Theranosticsmentioning
confidence: 99%
“…To overcome this limitation, manganese is a good substitute because of its inherent advantages, such as low intrinsic toxicity and effective positive contrast enhancement effect [ 117 , 118 ]. Wu et al [ 119 ] synthesized MPDA NPs (called MPDAPs) using the soft template method and then complexed Mn 2+ to obtain MPDAPs/Mn. In vitro infrared imaging analysis revealed that the photothermal conversion efficiency of MPDAPs/Mn was as high as 45.2%.…”
Section: Cancer Theranosticsmentioning
confidence: 99%
“…According to their result, the tumor ablation could be observed after MPDA-PEG-PTX treatment combined with 2 Wcm-2 laser irradiations for 5 min. In addition to chemo-photothermal therapy, MPDA could also be applied to immuno-photothermal, a combination of photothermal therapy and photodynamic therapy/chemodynamic therapy, as well as cancer theranostics ( Hu et al, 2019 ; Huang et al, 2021 ; Wu et al, 2021 ). However, few studies have illustrated the potential toxicity of MPDA so far, which blocked further clinical application.…”
Section: Discussionmentioning
confidence: 99%
“…The therapeutic process could be monitored by T 2 ‐weighted MRI and an infrared thermal camera. More recently, polydopamine‐coated mesoporous silica particles loaded with manganese ions were proven to be potent T 1 MRI CAs and photosensitizing agents with excellent PTCE in an in vivo mice model 79 . Beik and coworker established a computational model to simulate the heat transfer process in the tumor during PTT, based on MRI data and nanoparticle distribution in vivo.…”
Section: Theranostics For Mri‐guided Thermal Therapymentioning
confidence: 99%